Analisis Pengelolaan Dana Bantuan Operasional Satuan Pendidikan (BOSP) Di SD Negeri Emereuw Kota Jayapura - Ulukyanan, Sindi; Kambuaya, Maylen K. P; Sesa, Pascalina V. S (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2024)
This research was conducted to know the management of educational unit operational assistance funds (BOSP), financial reporting, accountability, transparency, internal and external inhibiting factors, as well as efforts to overcome external and internal inhibiting factors carried out by the Education Unit Operational Assistance Fund (BOSP) Team at Emereuw Public Elementary School, Jayapura City. This type of research uses a quantitative descriptive type, data collection techniques using interview guide methods, and documentation with the participants of this study, namely Principals, Treasurers, Operators, and Teachers. The results showed that the internal causes of delays were Human Resources (HR), which still required full attention from the school, especially the treasurer of BOSP funds in specific areas, the need for training and development of human resources (HR), Accuracy in tasks and responsibilities, increasing discipline in supervision, improving coordination and communication between parties involved in the management and reporting process. Factors causing external delays include the school budget activity planning application system (ARKAS); schools also experience problems in running applications used by schools, so they need to follow technical guidance from the relevant Office. When a treasurer of the education unit operational assistance fund (BOSP) or a school staff member is responsible for financial and administrative reporting, having a role in managing these tasks is an important factor in ensuring the efficiency and accuracy of reporting to avoid delays in education unit operational assistance funds (BOSP) at SD Negeri Emereuw.